2003
DOI: 10.1002/chin.200341281
|View full text |Cite
|
Sign up to set email alerts
|

Metal Ion Catalyzed Autoxidation Reactions: Kinetics and Mechanisms

Abstract: For Abstract see ChemInform Abstract in Full Text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…The sulfate ion radical (SO 4 –• ) is a very reactive species that plays a central role as an intermediate in a number of reaction systems, most notably the autoxidation of sulfur­(IV) , or one-electron oxidations using the peroxomonosulfate ion. , The iodide ion is also known to catalyze the aqueous autoxidation of sulfur­(IV); therefore, directly measuring the kinetics of the reaction between SO 4 –• and I – was important. It was found that the sulfate ion radical can be most favorably generated through the photolysis of a peroxodisulfate ion (S 2 O 8 2– ) initiated by a laser pulse at 266 nm In the presence I – , the following reaction takes place As a subsequent step, iodine atoms (I • ) give iodine molecule ions (I 2 –• ) with excess I – in a reversible process In the last step, I 2 –• recombines to give triiodide ions (I 3 – ) and I – Reactions and are also highly important in the aqueous photochemistry of I – . ,, The progress of reaction is primarily determined by the laser power.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The sulfate ion radical (SO 4 –• ) is a very reactive species that plays a central role as an intermediate in a number of reaction systems, most notably the autoxidation of sulfur­(IV) , or one-electron oxidations using the peroxomonosulfate ion. , The iodide ion is also known to catalyze the aqueous autoxidation of sulfur­(IV); therefore, directly measuring the kinetics of the reaction between SO 4 –• and I – was important. It was found that the sulfate ion radical can be most favorably generated through the photolysis of a peroxodisulfate ion (S 2 O 8 2– ) initiated by a laser pulse at 266 nm In the presence I – , the following reaction takes place As a subsequent step, iodine atoms (I • ) give iodine molecule ions (I 2 –• ) with excess I – in a reversible process In the last step, I 2 –• recombines to give triiodide ions (I 3 – ) and I – Reactions and are also highly important in the aqueous photochemistry of I – . ,, The progress of reaction is primarily determined by the laser power.…”
Section: Resultsmentioning
confidence: 99%
“…Inspired by the seminal work of Alan Turing on morphogenesis (shape formation in biological systems), 21 reaction−diffusion systems have already proved very useful in interpreting chemical and biological pattern formation 22−24 as well as other nonlinear dynamic phenomena such as oscillation, chaos, or self-organizing systems up to the most recent literature studies. 25 ) is a very reactive species that plays a central role as an intermediate in a number of reaction systems, most notably the autoxidation of sulfur(IV) 31,32 or one-electron oxidations using the peroxomonosulfate ion. 33,34 The iodide ion is also known to catalyze the aqueous autoxidation of sulfur(IV); 35 therefore, directly measuring the kinetics of the reaction between SO 4 −• and I − was important.…”
Section: ■ Introductionmentioning
confidence: 99%